The Role of Genetic Testing in Preventing Cardiovascular Diseases - Hafiz Muhammad Sohaib; Aamir Farid; Muhammad Zubair Ali; Rahool Kumar; Dr. Samar Ekram (Research Journal of Psychology, 2025)
Cardiovascular diseases (CVDs) are still the most common cause of death globally, and early prevention and detection are essential to limiting their effects. The purpose of this research was to assess the potential of genetic testing in the prevention of cardiovascular diseases in patients at the District Headquarters Hospital Lodhran. 100 patients with CVD risk factors were enrolled and received thorough clinical evaluation, biochemical profiling, and panelized genetic testing targeting the most relevant genes for cardiovascular risk, such as LDLR, APOB, PCSK9, MYH7, MYBPC3, and CYP2C19. Analysis identified that 32% of the patients had pathogenic or likely pathogenic variants that are associated with higher cardiovascular risk. The most prevalent mutations were in LDLR and APOB genes, linked to familial hypercholesterolemia, and CYP2C19 polymorphisms that impact the efficacy of antiplatelet therapy. Those with genetic mutations had significantly elevated levels of LDL cholesterol and family histories of premature cardiovascular events. Genetic testing informed individualized interventions including maximized lipid-lowering treatment and individualized antiplatelet regimens. The report emphasizes the practicability and clinical value of introducing genetic testing in a district hospital environment within Pakistan, in spite of limited resources and poor public awareness. Integrating genetic screening into standard cardiovascular practice can facilitate early diagnosis, risk stratification, and prevention of disease, reducing overall burden of disease. Wider access to genetic services and education of patients are key measures to advance cardiovascular outcome in the region.